An Evaluation of Maleic‐Itaconic Copolymers as Urease Inhibitors. Issue 4 (10th May 2018) - Mazzei, Luca; Broll, Valquiria; Ciurli, Stefano
Abstract : Core Ideas: Maleic‐Itaconic Polymers (MIPs) strongly and rapidly inactivate urease at pH 5.0. MIPs favour the release of the essential Ni(II) ions from the active site of urease. The urease inactivation by MIPs is comparable with that attained using NBPT. Urea hydrolysis in soil is accelerated 10 15 –fold by the nickel‐dependent enzyme urease to yield a source of N that can be assimilated by plants. This reaction determines an overall soil pH increase and significant ammonia volatilization, decreasing the efficiency of urea‐based fertilization. A control of urease activity is thus required for agronomic purposes. Maleic‐Itaconic Polymers (MIPs) have been claimed to decrease the N loss as ammonia volatilization by inhibiting urease activity. To investigate this matter, we performed an in vitro study using urease from jack bean ( Canavalia ensiformis, JBU) at pH 7.5 and pH 5.0. Urease is not affected by MIPs at pH 7.5, but the enzyme is completely inactivated in 20 min at pH 5.0 using MIPs in the 0.4 to 2.4 μmol L –1 range. This inactivation is comparable to that attained using similar concentrations of N ‐( n ‐butyl)‐thiophosphoric triamide (NBPT). In vivo assays conducted using Sporosarcina pasteurii as a model for a widespread soil bacterium and urea, in the presence of either MIPs or NBPT at pH 7.5, revealed that NBPT significantly inhibits both cellular growth and urease activity, while MIPs have no effect. To elucidate the mechanism of extracellular urease inactivation by MIPs in vitro, their Ni(II) sequestration capability was investigated. The MIPs (50 μmol L –1 ) completely extract the essential Ni(II) ions from the active site of urease at pH 5.0, in 3 h. This phenomenon is related to the capability of MIPs to shift the Ni(II)‐urease dissociation equilibrium through binding and chelation of the Ni(II) ions off the active site.